Auditoría Financiera al Gobierno Autónomo Descentralizado Parroquial de Malacatos del Cantón y Provincia de Loja, Periodo 2021. - Ochoa Soto, Jimmy Alexander (2023)
The research work called FINANCIAL AUDIT TO THE DECENTRALIZED AUTONOMOUS GOVERNMENT OF MALACATOS PARISH, LOJA CANTON AND PROVINCE, PERIOD 2021, was developed based on the Academic Regulations of the Universidad Nacional de Loja, as a previous requirement to obtain the degree and title of Accounting and Auditing Engineer - Certified Public Accountant, which was developed with the purpose to achieve the objectives set, in addition with the purpose to provide a contribution to the directors of the institution through the results achieved. For the development of the audit, it was carried out a previous visit to the Decentralized Autonomous Government of Malacatos Parish in order to gather relevant information about the situation of the institution, then it was carried out the evaluation of the internal control system through the application of questionnaires, in order to determine the level of risk and confidence for each of the components that were analyzed. Additionally, it was possible to verify the compliance with the applicable regulations in force and generally accepted accounting principles, through the implementation of the procedures established in the audit programs where the working papers were carried out, which allowed to determine the reasonability of the balances presented in the financial statements, thus providing as results that the institution has not carried out surprise cash audits, the institution does not take measures to safeguard collected funds, it does not carry out monthly bank reconciliations, only machinery and vehicles are insured, long-lived assets in poor condition are not written off, account balances are not reconciled, and obligations are not paid in a timely way. After carrying out the whole financial audit process, the audit report was drafted, showing the results obtained, which includes the comments, conclusions and recommendations of the findings detected in order to contribute to the authorities of the Decentralized Autonomous Government of Malacatos Parish to improve the financial management, accounting and internal control system implemented in the institution.